Google Trends Analytics dalam Bidang Pangan - Peradnya Dewi, Anak Agung Istri Agung; Arisena, Gede Mekse Korri; Fajarini, Luh Dian Rna (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
Food consumption behavior is influenced by market dynamics and socio-religious momentum, which is reflected in online information search activities. This study aims to analyze trends in staple food–related search keywords during periods of market volatility and major religious holidays using Google Trends data analyzed through the FineBI platform. The commodities examined include rice, granulated sugar, cooking oil, beef, shallots, eggs, milk, liquefied petroleum gas (LPG), and salt across five highly populated provinces in Indonesia, namely Bali, West Java, North Sumatra, West Kalimantan, and South Sulawesi. This study employs a descriptive quantitative approach using relative search index data from Google Trends (scale 0–100) over the last 12 months and the past five years. The results indicate that during periods of market volatility, the most consistent increases in search interest occurred for rice, cooking oil, granulated sugar, and beef, with relatively higher intensity in West Java and North Sumatra. In contrast, eggs, shallots, milk, and salt exhibited more moderate fluctuations, while LPG showed relatively stable search interest. During religious holiday periods, search interest increased most notably ahead of Eid al-Fitr, Christmas, and the Lunar New Year, whereas Galungan and Nyepi had more limited and region-specific impacts, particularly in Bali. These findings confirm that the integration of Google Trends and FineBI is effective as a supporting indicator for monitoring spatial and temporal dynamics of food consumption.